Carried meningococci in the Czech Republic: a diverse recombining population. - Jolley, K; Kalmusova, J; Feil, E; Gupta, S; Musilek, M; Kriz, P; Maiden, M (2000)
Population and evolutionary analyses of pathogenic bacteria are frequently hindered by sampling strategies that concentrate on isolates from patients with invasive disease. This is especially so for the gram-negative diplococcus Neisseria meningitidis, a cause of septicemia and meningitis worldwide. Meningococcal isolate collections almost exclusively comprise organisms originating from patients with invasive meningococcal disease, although this bacterium is a commensal inhabitant of the human nasopharynx and very rarely causes pathological effects. In the present study, molecular biology-based techniques were used to establish the genetic relationships of 156 meningococci isolated from healthy young adults in the Czech Republic during 1993. None of the individuals sampled had known links to patients with invasive disease. Multilocus sequence typing (MLST) showed that the bacterial population was highly diverse, comprising 71 different sequence types (STs) which were assigned to 34 distinct complexes or lineages. Three previously identified hyperinvasive lineages were present: 26 isolates (17%) belonged to the ST-41 complex (lineage 3); 4 (2.6%) belonged to the ST-11 (electrophoretic type [ET-37]) complex, and 1 (0.6%) belonged to the ST-32 (ET-5) complex. The data were consistent with the view that most nucleotide sequence diversity resulted from the reassortment of alleles by horizontal genetic exchange.